2015
DOI: 10.1039/c4bm00303a
|View full text |Cite
|
Sign up to set email alerts
|

The transfection efficiency of calix[4]arene-based lipids: the role of the alkyl chain length

Abstract: The size, surface charge, and microstructure of lipoplexes comprising cationic lipids and nucleic acids are important factors for transfection efficiency. As these properties are largely determined by the cationic lipids used, a number of studies on the relationship between cationic lipids and the transfection efficiency have been reported. Among the many cationic lipids, lipids with multivalent cationic head groups are expected to be potent transfection reagents. Here, we prepared calix[4]arene-based lipids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…The calixarene scaffold represents a very versatile structure to build amphiphilic compounds due to the possibility of variably and selectively functionalizing both its upper (aromatic para positions) and lower (phenolic oxygens) rim. Moreover, the possibility of linking to the macrocyclic platform several binding moieties, resulting in preorganized arrays, gives rise to systems that, exploiting a multivalent effect, frequently show improved biological activity with respect to corresponding monovalent models. , From this point of view, also the tight compaction of hydrophobic chains located at one of the rims can result in the enhancement of some properties such as (self)­assembling capabilities in an aqueous environment. …”
Section: Introductionmentioning
confidence: 99%
“…The calixarene scaffold represents a very versatile structure to build amphiphilic compounds due to the possibility of variably and selectively functionalizing both its upper (aromatic para positions) and lower (phenolic oxygens) rim. Moreover, the possibility of linking to the macrocyclic platform several binding moieties, resulting in preorganized arrays, gives rise to systems that, exploiting a multivalent effect, frequently show improved biological activity with respect to corresponding monovalent models. , From this point of view, also the tight compaction of hydrophobic chains located at one of the rims can result in the enhancement of some properties such as (self)­assembling capabilities in an aqueous environment. …”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Sakurai et al reported amphiphilic calix[4]arenes 64-68 with four amino groups at the upper rim and different lengths of alkyl chains at the lower rim. Highest transfection efficiency was observed with 65 that bears a medium-length alkyl chain with six carbons 84. Furthermore, in the presence of phosphatidylserine micelles, DNA can be released from the co-assemblies of 65 and plasmid DNA, at pH 5 but not at pH 7.…”
Section: Amphiphilic Cas For Gene Deliverymentioning
confidence: 98%
“…Sakurai studied the transfection efficiency of amino‐modified C4A‐based lipids with different alkyl chain lengths (C3–C15, 70 – 74 ), revealing that 71 lipoplexes exhibited the highest efficiency, 73 and 74 lipoplexes featured slightly lower efficiencies, while 70 and 74 lipoplexes were not active [132] . The 71 , 72 , and 73 lipoplexes also exhibited low cytotoxicity.…”
Section: Gene Delivery and Transfectionmentioning
confidence: 99%